Rotational Structure of Weakly Bound Molecular Ions (Journal of Atomic and Molecular Sciences, 2018)
Relying on the quantization rule of Raab and Friedrich [Phys. Rev. A 80(2009) 052705], we derive simple and accurate formulae for the number of rotationalstates supported by a weakly bound vibrational level of a diatomic molecular ion.We also provide analytic estimates of the rotational constants of any such levels upto threshold for dissociation and obtain a criterion for determining whether a givenweakly bound vibrational level is rotationless. The results depend solely on the longrange part of the molecular potential.
Keywords: molecular ions; cold collisions; rotational states; near-threshold quantization; WKB; analytic models.